2005
DOI: 10.1111/j.1365-2125.2004.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic profiling across the irinotecan pathway in Asian patients with cancer

Abstract: AimsThe aim of this exploratory study was to investigate associations between irinotecan pharmacokinetic parameters and allelic variants in genes encoding for drug transpor ters and drug metabolizing enzymes that are involved in irinotecan disposition in Asian patients with cancer. MethodsIrinotecan was administered at 100 mg m -2 over 90 min on a weekly schedule to 29 nasopharyngeal carcinoma patients and pharmacokinetic analysis was per formed during the first cycle. All patients were genotyped for allelic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 27 publications
3
46
2
Order By: Relevance
“…64 However, the latter study also showed an association between the three-SNP haplotype and the C max of SN-38, a product of irinotecan hydrolysis, in the opposite direction to the association described with the single SNP.…”
mentioning
confidence: 92%
“…64 However, the latter study also showed an association between the three-SNP haplotype and the C max of SN-38, a product of irinotecan hydrolysis, in the opposite direction to the association described with the single SNP.…”
mentioning
confidence: 92%
“…Among other work examining the association between UGT1A1 genotype and cancer, a recent exploratory study examined the role of enzyme and transporter polymorphisms in irinotecan disposition in 29 nasopharyngeal carcinoma patients (Zhou et al, 2005). Of the 11 candidate genes studied, polymorphisms in the drug transporter genes were found to affect irinotecan disposition.…”
Section: Ugt1a1 Polymorphisms and Cancer: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Thus the lack of MDR1/Pgp in humans may be either early lethal (very unlikely) or harmless. In the case of ABCG2, individuals with genes coding for a nonfunctional ABCG2 (a truncated form of the protein) have been found in a low percentage (141,428), with no apparent disease condition. However, it has been suggested that drug hypersensitivity (188,242,251) and even alfalfa hypersensitivity (see Refs.…”
Section: B Innate Chemoimmunitymentioning
confidence: 99%